2018
DOI: 10.3390/en11040726
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of Hot-Spots in Photovoltaic Systems Using Distributed Power Electronics

Abstract: In the presence of partial shading and other mismatch factors, bypass diodes may not offer complete elimination of excessive power dissipation due to cell reverse biasing, commonly referred to as hot-spotting in photovoltaic (PV) systems. As a result, PV systems may experience higher failure rates and accelerated ageing. In this paper, a cell-level simulation model is used to assess occurrence of hot-spotting events in a representative residential rooftop system scenario featuring a moderate shading environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…2(a). Another reason that hot-spotted PV modules strongly depends on the environmental parameters such as strong wind speed (eventually cools down PV surface and reduce hot-spotting impact [40]), humidity variations and the ambient temperature [16], therefore, with such environmental conditions, the MPPT tracking accuracy might differ meaningfully.…”
Section: A Examined Pv Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…2(a). Another reason that hot-spotted PV modules strongly depends on the environmental parameters such as strong wind speed (eventually cools down PV surface and reduce hot-spotting impact [40]), humidity variations and the ambient temperature [16], therefore, with such environmental conditions, the MPPT tracking accuracy might differ meaningfully.…”
Section: A Examined Pv Modulesmentioning
confidence: 99%
“…Most recently, distributive MPPT method suggested by Coppola et al [15] and Olalla et al [16] are a conventional method to mitigate hot-spot in PV modules, with an approximate reduction up to 20 °C for small and medium hotspotting areas. On the other hand, Kim & Krein [17] show the "inadequateness" of the standard bypass diodes, the insertion of a series-connected switch are suited to interrupt the current flow during bypass activation process.…”
Section: Introductionmentioning
confidence: 99%
“…The higher resonant frequency f r was 164 kHz, and the prototype was operated at f s = 140 kHz with a dead time period of 0.4 µs. sufficient to preclude loss in annual energy yield in most cases [35,36]. As long as panels are installed in a proper location, severe shading conditions rarely occur.…”
Section: Prototypementioning
confidence: 99%
“…PV array reconfiguration can be obtained by means of a reconfigurable switch matrix made of MOSFETs or of electromechanical relays. In [26][27][28][29][30], it has been shown that distributed converters can improve system reliability by reducing the occurrence of hot spots. In fact, reliability represents a crucial aspect to take into account in PV applications.…”
Section: Introductionmentioning
confidence: 99%